A formação docente continuada sobre a educação para a sexualidade, em uma escola pública no município de Diadema: a ótica de professores participantes e gestora - Cisotto, Laurindo (2010)
The present work discusses the teacher continued education about the education to sexuality, in a public school from the county of Diadema (SP). In order to accomplish that, discussions were registered, testimonies were picked from the manager and teachers involved through questionnaires, interviews and continued education meetings. In these studies we sought to extend the concept of sexuality in order to overcome speculative discourses that crystallize notions and set stereotype or reduce this device to a preventive treatment to Sexually Transmitted Diseases, with centralization revolving the human anatomy. The theoretical foundation was based in authors from Critical and Post-Critical Theories, teacher continued education motivators, such as: Apple, Foucault, Freire, Giroux, Louro, Sacristán, Tardif, Silva, among other studious. In the inner parts of the schools, lives that are being constituted in subjectivity, in people sexual beings that are children, teenagers, educators, managers - develop and move around. This way, the sexuality question may be integrated to the curriculum. The results point to the comprehension that the teacher continued education is a challenge to be faced, especially about sexuality, in the way that we must produce new competences and abilities. It is desirable that the school builds its pedagogical project, constituted by the curriculum, in which it is possible to include the continued education theme in the sexuality issues in order to make it more porous and flexible to the new arrangements and conceptions, as a certain requirement transmitted by the contemporary society